Mirth as an Outlet of Repressed Feminine Yearnings in Carol Ann Duffy’s Poetry - Mary Louisa Lum (Mediterranean Journal of Social Sciences, 2022)
Subtlety is the only way wherein feminine rebellion can flourish and succeed in a male dominant society. This paper attempts to show that collaborative feminine effort leads to collective liberty and that Duffy (2002) pays homage to the feminist waves, especially the radical phase. The poet uses laughter as a metaphor to represent the feminist waves that were initially perceived as a joke but culminated in a force that ensured the emancipation of women. Although women’s desires are often repressed by the patriarchal machinery that seeks to oppress them, united action leads to liberation. Critics of Duffy have focused on her radical feminist and revisionist themes but this paper will also read the Laughter of Stafford Girls High (2002) as a homage to the various feminist waves that have contributed to women’s emancipation discourses globally. The paper draws from Wollstonecraft (1792) whose treatise A Vindication of the Rights of Woman exposed the triviality of women’s education and advocated for equality in learning. Although contemporary society enjoys parity in learning, several feminist critics like Howe (1977) and Hooks (1994) insist that there are still hidden messages within curriculums that tactfully ensure the marginal role of women. The absence of women in the canons gives the pervasive feeling that women have contributed nothing to human progress. The paper, therefore, aligns with the idea of feminine writing posited by Cixous (1976) as the only way through which women can write their unique history. From a reading of Duffy (2002) with the aforementioned theoretical leanings, it was realized that spaces of patriarchal brainwashing still abound despite the perceived progressive worldview. Equally, united action is important for the restitution of the rights of all women globally. Received: 7 September 2022 / Accepted: 27 October 2022 / Published: 5 November 2022